2016
DOI: 10.1111/andr.12306
|View full text |Cite
|
Sign up to set email alerts
|

Protective features of resveratrol on human spermatozoa cryopreservation may be mediated through 5’ AMP‐activated protein kinase activation

Abstract: Biochemical and physical modifications during the freeze-thaw process adversely influence the restoration of energy-dependent sperm functions required for fertilization. Resveratrol, a phytoalexin, has been introduced to activate 5' AMP-activated protein kinase which is a cell energy sensor and a cell metabolism regulator. The cryoprotection of resveratrol on sperm cryoinjury via activation of AMP-activated protein kinase also remains to be elucidated. Our aim, thus, was to investigate: (i) the presence and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 68 publications
1
59
0
Order By: Relevance
“…AMPK was expressed in the acrosome, midpiece and the entire flagellum of goat sperm, which was in consistence with that in boar [30], human [16,17] and chicken [15] sperm. However, this observation was different to the report by Swegen et al [31] who demonstrated that AMPK was predominantly present in the midpiece and the entire flagellum of stallion sperm.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…AMPK was expressed in the acrosome, midpiece and the entire flagellum of goat sperm, which was in consistence with that in boar [30], human [16,17] and chicken [15] sperm. However, this observation was different to the report by Swegen et al [31] who demonstrated that AMPK was predominantly present in the midpiece and the entire flagellum of stallion sperm.…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, AMPK inhibition led to a significant decrease in motility, mitochondria membrane potential and acrosome integrity during long-term storage of boar semen [21]. However, Shabani Nashtaei et al demonstrated that AMPK inhibition did not affect membrane integrity in human sperm [17]. Moreover, Cordova et al [14] reported that addition of neither AMPK activators nor AMPK inhibitors to the freezing extenders affected motility, membrane integrity and acrosome integrity in stallion sperm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between metabolism and fertility are well established, particularly in the female. Recent discoveries show that AMPK is also present in male gonad and spermatozoa in different species [Caenorhabditis elegans (Lee et al, 2008), oyster (Guevelou et al, 2013), chicken (Nguyen et al, 2014), boar (Hurtado de Llera et al, 2012, 2013), mouse (Tanwar et al, 2012; Tartarin et al, 2012), stallion (Cordova et al, 2014), and human Calle-Guisado et al, 2016; Shabani Nashtaei et al, 2016]. It is these roles in male gonad and spermatozoa that I will now describe.…”
Section: Structure and Expression Of Ampkmentioning
confidence: 99%
“…Furthermore, the presence of AMPK, especially in its active form, phospho-AMPK-Thr172, was highlighted in spermatozoa of boar, stallion, mouse, chicken and human (Hurtado de Llera et al, 2012, 2013; Tartarin et al, 2012; Cordova et al, 2014; Nguyen et al, 2014; Calle-Guisado et al, 2016; Shabani Nashtaei et al, 2016). In boar, the phospho-AMPK form is mainly localized in the acrosome, the sub-equatorial segment of the head and in the intermediate part (Hurtado de Llera et al, 2013).…”
Section: Role Of Ampk In Male Gonad and Sperm Productionmentioning
confidence: 99%